2006
DOI: 10.2106/jbjs.f.00587
|View full text |Cite
|
Sign up to set email alerts
|

Early Diagnosis of Ceramic Liner Fracture

Abstract: Preparative steps for synovial fluid analysis. Tlie filter is placed on the holder, synovial fluid is added (a), digestion is performed with sodium hypochlorite (b), water is flushed through the filter, and the filter is dried (c).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 16 publications
1
85
0
Order By: Relevance
“…Synovial fluid samples were obtained either intra-operatively, after the joint was exposed during revision surgery (carefully avoiding dilution with blood from the surgical dissection), or by using an ultrasound-guided hip needle aspiration according to a published guideline [19] and then stored at −80°C until the analysis was performed.…”
Section: Detection Of Particles In Synovial Fluidmentioning
confidence: 99%
“…Synovial fluid samples were obtained either intra-operatively, after the joint was exposed during revision surgery (carefully avoiding dilution with blood from the surgical dissection), or by using an ultrasound-guided hip needle aspiration according to a published guideline [19] and then stored at −80°C until the analysis was performed.…”
Section: Detection Of Particles In Synovial Fluidmentioning
confidence: 99%
“…Although mechanistic information regarding fracture of ceramic liners is currently minimal, component impingement is believed to be a/the principal risk factor [14,17,23,28,36]. Component malpositioning [13], microseparation leading to edge loading [33], incomplete seating of modular liners [22], and obesity [30] have also been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…This, together with late manifestation on radiographs, led to delayed diagnosis. Toni et al 14 found a positive correlation between ceramic liner fracture and a noisy hip on clinical examination. They recommended computed tomography (CT) and joint aspiration in any snapping hip after ceramic THA to rule out early failure.…”
Section: Discussionmentioning
confidence: 98%